2022
DOI: 10.1088/1748-9326/ac6a6a
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of El Niño on the South China Sea surface salinity as seen from satellites

Abstract: The impacts of El Niño on sea surface salinity (SSS) in the South China Sea (SCS) are investigated using satellite observations, in-situ data, and reanalysis products. Here, we show that positive SSS anomalies cover most of the SCS during the mature phase of El Niño. The physical processes controlling these positive SSS anomalies are different from region to region, and the differences are especially obvious between the northern and southern SCS. In the northern SCS, the positive SSS anomalies are primarily ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Bersinggungan dengan LCS memberikan Laut Natuna Utara memiliki massa air yang kompleks, dengan musim yang mempengaruhi kondisi interaksi laut dan atmoster (Hariyadi et al, 2021), yang memiliki karakteristik iklim mengikuti Pasifik tengah katulistiwa (Liu et al, 2002). El Nino Southern Oscillation (ENSO) berkontribusi dalam meningkatnya salinitas di LCS (Qi et al, 2022), begitu pula dengan probabilitas pusaran pilin tertutup pada fase dewasa (Zu et al, 2019). Nampaknya, Indian Ocean Dipole (IOD) juga memiliki peranan dalam kompleksitas suhu permukaan laut dan presipitasi di sekitar Laut Natuna Utara dan LCS (Khaldun et al, 2018).…”
Section: Pendahuluanunclassified
“…Bersinggungan dengan LCS memberikan Laut Natuna Utara memiliki massa air yang kompleks, dengan musim yang mempengaruhi kondisi interaksi laut dan atmoster (Hariyadi et al, 2021), yang memiliki karakteristik iklim mengikuti Pasifik tengah katulistiwa (Liu et al, 2002). El Nino Southern Oscillation (ENSO) berkontribusi dalam meningkatnya salinitas di LCS (Qi et al, 2022), begitu pula dengan probabilitas pusaran pilin tertutup pada fase dewasa (Zu et al, 2019). Nampaknya, Indian Ocean Dipole (IOD) juga memiliki peranan dalam kompleksitas suhu permukaan laut dan presipitasi di sekitar Laut Natuna Utara dan LCS (Khaldun et al, 2018).…”
Section: Pendahuluanunclassified
“…A low salinity tongue extends from the Southern part of the SCS, reaching as far as 10°N, which is closely related to the freshwater discharge from the Mekong and Rajang Rivers. Due to its special geographical location, the spatial distribution of the salinity in the SCS has significant features which are closely related to El Niño-Southern Oscillation (ENSO) [16][17][18][19], Asian monsoons, and the Pacific Western boundary current system [15,20]. Previous studies have suggested that the variability of the salinity in the SCS has a significant influence on the regional circulation and climate changes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Extended continental shelves exist along the north boundary and southwest boundary, while the deeper water is oriented in a southwest-northeast direction across the central part of the SCS [12]. Due to its unique geographical location and complicated dynamical features, the temperature structures in the SCS have remarkable characteristics associated with El Niño-Southern Oscillation (ENSO) [13], Asian monsoon and Pacific western boundary current system [14,15], which have a far-reaching influence on the regional and global climate [16,17]. In the climatological mean, sea surface temperature (SST) in the SCS shows a chiefly southwest-northeast oriented pattern, which is gradually increasing southward (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%